Advances in pharmacology. - August, J. Thomas (Advances in pharmacology, 1999)
Advances in Pharmacology provides a rich collection of reviews on timely topics. Emphasis is placed on the molecular bases of drug action, both applied and experimental. For easy reference, this volume provides a cumulative subject index covering Volumes 25-44.